Penerapan model problem based learning (PBL) berbantuan media iSpring pada materi larutan elektrolit dan non elektrolit - Feronica Felentina; Agus Kembaren (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to determine the average learning outcomes and learning motivation with the iSpring Media Assisted Problem Based Learning (PBL) learning model compared to conventional learning models. This research was conducted at SMA Negeri 1 Sunggal with the samples in this study were 2 classes, namely the experimental class in class X IPA 2 and the control class in class X IPA 3 which were obtained using purposive sampling technique. The research instrument consisted of a test instrument in the form of validated questions and a non-test instrument in the form of a learning motivation questionnaire. The results of the study for learning motivation using the independent sample t-test at = 0.05, the tcount value was 1.81. The results of the study on learning outcomes showed that the average value with the Problem Based Learning (PBL) learning model was 84.58 while the average value in the conventional learning model was 77.50. The gain calculation shows that the increase in learning outcomes in the experimental class is 72% with criteria while the control class is 68% with moderate criteria. From the results of the study, it was obtained that the tcount value was 4.94 Ha, which was accepted, namely the learning outcomes of students who were taught with the Problem Based Learning learning model assisted by the Ispring media were higher than the learning outcomes of students who were taught using conventional learning models on electrolyte and non electrolyte solutions. While the research results for the correlation test is 0.333. Thus, there is a significant correlation between learning motivation to increase student learning outcomes in the experimental class by 11%. This shows that the higher the motivation, the higher the learning outcomes, and vice versa.